A Carbon-Based Nanomaterial with Dichotomous Effects: Antineoplastic on Oral Cancer Cells and Osteoinductive/Chondroinductive on Dental Pulp Stem Cells - Milica Jaksic Karisik; Nataša Jović Orsini; Jelena Carkic; Milos Lazarevic; Dijana Mitić; Bojan Jokanovic; Vukoman Jokanović; Jelena Milasin (Journal of Functional Biomaterials)
Background: Oral cancer is an aggressive malignancy with modest survival rates. It also causes disfigurement following surgical removal of the tumor, thus highlighting the need for new cancer treatment and tissue repair modalities. Carbon-based nanomaterials have emerged as promising tools in both anticancer and regenerative therapies. Objectives: We aimed to synthesize a new carbon-based nanomaterial (CBN) and test its antineoplastic effects, as well as its potential regenerative capacity. Materials and Methods: A carbon nanomaterial, obtained by ball milling graphite flakes, was functionalized with polyvinylpyrrolidone (CBN/PVP). Its physicochemical properties were explored with X-ray diffraction (XRD), attenuated total reflection–Fourier transform infrared spectroscopy (ATR-FTIR), micro-Raman spectroscopy, fluorescent and scanning electron microscopy, and wettability analysis. For the antineoplastic effects investigation, oral cancer cells were treated with CBN/PVP and examined with MTT and migration assays, as well as cell-cycle and ROS production analyses. Gene expression was determined by qPCR. To examine the pro-regenerative capacity of CBN/PVP, dental pulp stem cell cultures (DPSCs) were treated with the nanomaterial and subjected to osteo- and chondro-induction. Results: Lower concentrations of CBN/PVP (50, 100 μg/mL) applied on cancer cells exerted remarkable cytotoxic effects, induced G1 cell-cycle arrest, and reduced cancer cell invasion potential by different mechanisms, including downregulation of the PI3K/AKT/mTOR pathway. In contrast, the addition of 50 µg/mL of CBN/PVP to DPSCs stimulated their survival and proliferation. CBN/PVP significantly enhanced both the osteogenic (p < 0.05) and chondrogenic (p < 0.01) induction of DPSCs. Conclusions: The novel carbon-based nanomaterial displays unique characteristics, making it suitable in anticancer and regenerative therapies concomitantly.